Application of structural building information modeling (S-BIM) for sustainable buildings design and waste reduction: A review - Umar, U.A. (Research India Publications, 2016)
Strategies of sustainable reasoning are in many ways historical. When buildings from some of the indigenous cultures are examined, it can be easily observed that they were highly competent at adapting the location and materials of the structures to the climate. As time passes and civilizations grew static, buildings took on different values. Structural Building Information Modeling (S-BIM) enables structural engineers and designers to develop structural models for steel, concrete and timber buildings with flexibility; examine engineering alternatives; create smarter well-informed design decisions; and anticipate costs and overall performance. By using Building Information Modeling (BIM), pre-requisites for drawings are reduced. Technical details are regularly updated and easily obtained from the model, which provide designers the platform to resolve design issues and allow team members access to view the plans. BIM stores data for all aspects of the building, which include structural; architectural; mechanical, electrical and plumbing (MEP); and landscape data before and during post-construction phases. The paper reviews advantages of S-BIM application for sustainable building design and waste reduction as acknowledged by experts from the construction industry and recommends anticipated outcomes for improvement to the Architecture, Engineering and Construction (AEC) industry. Â© Research India Publications.